2022
DOI: 10.3389/feduc.2022.902237
|View full text |Cite
|
Sign up to set email alerts
|

Are There Enough Open Educational Resources Dealing With Social Science Research Methods? Insights From the D-A-CH Region

Abstract: The D-A-CH (Germany, Austria, and Switzerland) region has traditionally been skeptical toward open educational resources (OER) materials. Despite being strong partners for the open science community, the three German-speaking countries in Europe did not embrace wide-reaching OER policies in the past and offered only a limited number of incentives for supranational or nationwide genuine German-language OER. These missing national initiatives can also be seen in the field of social science research-related mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…Some institutions had limited resources to access educational materials online (Bao, 2020;Kerres, 2020;Prandner & Forstner, 2022). Naylor and Nyanjom (2021) reported that faculty found instructional support beneficial and critical when transitioning to online learning.…”
Section: Technical and Institutional Supportmentioning
confidence: 99%
“…Some institutions had limited resources to access educational materials online (Bao, 2020;Kerres, 2020;Prandner & Forstner, 2022). Naylor and Nyanjom (2021) reported that faculty found instructional support beneficial and critical when transitioning to online learning.…”
Section: Technical and Institutional Supportmentioning
confidence: 99%